Diversity and biogeographical patterns of yeast communities in Antarctic, Patagonian and tropical lakes. (August 2017) - Brandão, Luciana R.; Vaz, Aline B.M.; Espírito Santo, Lilia C.; Pimenta, Raphael S.; Morais, Paula B.; Libkind, Diego; Rosa, Luiz H.; Rosa, Carlos A.
Abstract: We investigated the distribution patterns of yeast communities in freshwater lakes along a latitudinal gradient in order to evaluate yeast biogeography at intercontinental (501–8000 km), regional (0–500 km) and local (0–1 km) geographical scales. We identified 285 yeast isolates belonging to 64 species based on sequence analysis of the ITS-5.8S region and the D1/D2 domains of the large subunit of rRNA genes. Distance decay analysis showed a significant negative slope curve at the intercontinental scale. At the intercontinental and regional scales, the dissimilarity of the yeast communities was correlated with geographical distance, with community similarity decreasing with increasing distance. The physiological profiles of the yeast communities from tropical and Patagonian lakes were similar but were different from those of Antarctic lakes. This is the first report of latitudinal patterns of lake yeast diversity along a gradient extending from Antarctic to tropical environments. Highlights: The biogeography of cultivable yeasts in a latitudinal gradient was evaluated. Identified 285 yeast isolates by sequencing of ITS region and D1/D2 domains. Yeast communities associated with the lakes studied were not randomly distributed. Yeast community similarity decreased with increasing geographic distance.